Contribution of sulfuric acid and oxidized organic compounds to particle formation and growth - F. Riccobono; L. Rondo; M. Sipilä; P. Barmet; J. Curtius; J. Dommen; M. Ehn; S. Ehrhart; M. Kulmala; A. Kürten; J. Mikkilä; P. Paasonen; et al. (Atmospheric Chemistry and Physics, 2012)
Lack of knowledge about the mechanisms underlying new particle formation and their subsequent growth is one of the main causes for the large uncertainty in estimating the radiative forcing of atmospheric aerosols in global models. We performed chamber experiments designed to study the contributions of sulfuric acid and organic vapors to the formation and early growth of nucleated particles. Distinct experiments in the presence of two different organic precursors (1,3,5-trimethylbenzene and α-pinene) showed the ability of these compounds to reproduce the formation rates observed in the low troposphere. These results were obtained measuring the sulfuric acid concentrations with two chemical ionization mass spectrometers confirming the results of a previous study which modeled the sulfuric acid concentrations in presence of 1,3,5-trimethylbenzene. New analysis methods were applied to the data collected with a condensation particle counter battery and a scanning mobility particle sizer, allowing the assessment of the size resolved growth rates of freshly nucleated particles. The effect of organic vapors on particle growth was investigated by means of the growth rate enhancement factor (Γ), defined as the ratio between the measured growth rate in the presence of α-pinene and the kinetically limited growth rate of the sulfuric acid and water system. The observed Γ values indicate that the growth is already dominated by organic compounds at particle diameters of 2 nm. Both the absolute growth rates and Γ showed a strong dependence on particle size, supporting the nano-Köhler theory. Moreover, the separation of the contributions from sulfuric acid and organic compounds to particle growth reveals that the organic contribution seems to be enhanced by the sulfuric acid concentration. Finally, the size resolved growth analysis indicates that both condensation of oxidized organic compounds and reactive uptake contribute to particle growth.